2020
DOI: 10.1017/s104161022000109x
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral pattern of patients with frontotemporal dementia during the COVID-19 pandemic

Abstract: The behavioral pattern of patients with frontotemporal dementia during the COVID-19 pandemic How the coronavirus 2019 pandemic affects patients with frontotemporal dementia?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 10 publications
1
37
0
Order By: Relevance
“…The evidence presented is based on qualitative (n = 8), quantitative (n = 27), and mixed methods (n = 5) research. Studies have been conducted almost exclusively online or by phone (only Suzuki et al [2020] explicitly reported the possibility of face-to-face interviews). Most studies used convenience samples (n = 29), but some analyzed nationally representative datasets (n = 11).…”
Section: Resultsmentioning
confidence: 99%
“…The evidence presented is based on qualitative (n = 8), quantitative (n = 27), and mixed methods (n = 5) research. Studies have been conducted almost exclusively online or by phone (only Suzuki et al [2020] explicitly reported the possibility of face-to-face interviews). Most studies used convenience samples (n = 29), but some analyzed nationally representative datasets (n = 11).…”
Section: Resultsmentioning
confidence: 99%
“…( Elshazli et al, 2020 ) Finally, people with dementia, due to the nature of their cognitive decline, would require the care and support of carers such as dementia caregivers in order to be able to follow healthcare and preventive measures such as wearing face masks and washing their hands with water and soap or hand sanitizers. ( Suzuki et al, 2020 ) However, during this COVID-19 pandemic, the availability of caregivers becomes limited which may cause dementia patients unable to follow healthcare and preventive measures therefore making them posed a higher risk of contracting an infection from COVID-19. ( Dang et al, 2020 )…”
Section: Discussionmentioning
confidence: 99%
“…These must be taken into account in order to overcome the challenges related to the delivery of effective care strategies for people with dementia in the last phases and after the end of this pandemic. Future studies in larger cohorts, with more robust designs and theory-grounded will be needed to gain more knowledge about the short-term and long-term biological and psycho-social effects of the COVID-19 pandemic on mental health of specific vulnerable populations of older adults, e.g., people with non-AD dementias that may present with more severe behavioural problems (56,57), and to ascertain the biological and psychosocial mechanisms that may explain these findings, as well as the possible risk/protective factors.…”
Section: Neuropsychiatric Symptoms In People In Social Isolation Due mentioning
confidence: 99%